Library-led forums on broadband: an inquiry into public deliberation - Schenck-Hamlin, Donna C.; Han, Soo-Hye; Schenck-Hamlin, William (My University, 2014)
Access to high-speed (broadband) Internet in public libraries requires a well-informed public to advocate, particularly in periods of government funding reductions and rapid technical and regulatory change. Libraries are encouraged by the National Broadband Plan to facilitate public inquiry on this issue by holding participatory forums. To collect evidence of the potential public response to library-led forums on this topic using a deliberative protocol, researchers conducted pre- and postforum surveys and content-analyzed recorded transcripts from thirteen library forums in north central Kansas. Results show positive influences of deliberation on participants’ information seeking, political self-efficacy, subsequent issue advocacy, and general satisfaction with the forum experience.
Keywords: Broadband; High-speed internet; Forums